OUTLOOK OF CHINA’S STATE-OWNED ENTERPRISES TANSFORMATION - Hu, Yi (European Scientific Journal, ESJ, 2014)
This paper created a framework for a dynamic institutional analysis. (1) Reduction of the conviction and motivation inside economic factors (We think that this is the inducing factors of system changes), (2) system changes will be ultimately beneficial to the efficiently allocation of resources, (3) the typical economic factors. This is from the old institutional analysis framework, Mr. Frank Knight's economic thought and historical materialism. Based on this analytical framework, we researched Transformation of China's state-owned enterprises, we come to conclusion that it is the time for the market forces play an basic role in the allocation of resources.